(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Two popular forms of rechargeable batteries with different properties and uses are lead-acid and lithium ferro phosphate (LiFePO4) batteries. In backup power systems and automotive starting, lighting, and ignition (SLI) applications, they are frequently utilised and appropriate for applications that demand high discharge currents. However, in comparison to LiFePO4 batteries, lead-acid batteries have a shorter cycle life, lower charging efficiency, and require more maintenance. Conversely, LiFePO4 batteries outperform lead-acid batteries in terms of charging efficiency, cycle life, and energy density. Additionally, they are less heavy and have a slower rate of self-discharge, which makes them perfect for renewable energy storage systems, electric cars, and portable electronics. LiFePO4 batteries frequently offer better long-term value because of their superior performance and longer longevity, even though they are more expensive initially. The use of hazardous substances like lead and sulphuric acid in lead-acid batteries raises more environmental issues because these materials can pollute the environment if improperly disposed of or recycled. In contrast, LiFePO4 batteries are said to be more environmentally friendly because they don’t contain heavy metals and are less likely to catch fire or experience thermal runaway. In summary, although lead-acid batteries offer benefits in specific uses, LiFePO4 batteries are the better option for many contemporary energy storage requirements due to their higher performance, longer lifespan, and less negative environmental impact. The choice between these two battery technologies, however, ultimately comes down to particular needs like price, weight, energy density, and environmental factors.